Delayed Poroelastic Triggering of the 2016 October Visso Earthquake by the August Amatrice Earthquake, Italy. Issue 5 (8th March 2018) - Tung, S.; Masterlark, T.
Abstract: Two months after the 2016 Amatrice earthquake (AE), a strong (~ M 6) earthquake (Visso earthquake, VE) struck the town Visso, Italy, 20 km north of the AE epicenter. Between these two events, the aftershocks migrated gradually toward to the VE epicenter at a rate of ~0.4 km/d, indicating propagation of pore pressure front. We use finite element models to simulate the postseismic fully coupled poroelastic response. The results show that the pore fluid flows (up to 50 nm/s) both horizontally and vertically into the VE hypocenter since the AE and destabilized the area with extra ~70% of Coulomb failure stress. Majority of nearby aftershocks (>80%) tend to cluster within the zones of coseismic depressurization where fluid flow converges. A maximum ΔCFS of ~35 kPa is calculated at the VE hypocenter during its rupture by a crustal permeability, 10 –16 ± 0.7  m 2, suggesting that an intermediately fractured crust allows maximum rupture tendency for the VE during poroelastic fluid recovery. Key Points: Visso earthquake and nearby faults were destabilized with increasing Coulomb stress induced by pore fluid currents after Amatrice earthquake Aftershock migration and clustering are found within the areas of coseismic depressurization and postseismic fluid inflow Time delay and location of the Visso earthquake are poroelastically favored by intermediately fractured crust